Ação da serinoprotease PIC produzida por escherichia coli sobre proteínas da matriz extracelular e da cascata de coagulação sanguínea - GOMES, Janaína Vasconcelos (2019)
Serine protease Pic (protein involved in colonization) is an autotransporter protein identified in enteroaggregative E. coli (EAEC), Shigella flexneri and Citrobacter rodentium. Among biological roles for Pic have been described hemagglutination, mucinolytic activity, factor V degradation of the coagulation cascade and cleavage of leukocyte surface glycoproteins, which are involved in trafficking, migration and inflammation. Our research group has already demonstrated its performance in the human complement system, which gives these bacteria the ability to circumvent the defense mechanisms of the innate immune system, thus favoring the development and maintenance of sepsis. Because of these abilities, it was hypothesized that Pic would have action on other important host molecules such as the proteins involved with the blood clotting cascade and extracellular matrix molecules. Thus, the objective of this study was to investigate the action of Pic serinoprotease on components of the extracellular matrix and blood coagulation cascade. For this, concentrated fractions of Pic (HB101 / Pic) and non-Pic (HB101) -producing E. coli culture supernatants as well as BSA were incubated at different times with several molecules of the blood coagulation cascade (plasminogen, fibrinogen and fibrin) and extracellular matrix (collagen type I, collagen type IV, decorin, laminin and plasma fibronectin) to evaluate both a possible binding and the degradation of these components. In addition, a plasmin activation assay was performed in plasmin, as this is a key molecule in the formation of clots and in the activation of other pathways of the immune system. In this way, it was possible to observe that the concentrated fractions of HB101 / Pic culture supernatants were able to bind to several extracellular matrix molecules in a significant manner, such as collagens type I and IV, laminin and fibronectin. By incubating the Pic protein with blood coagulation molecules, it was possible to observe binding with plasminogen, which in turn was converted into its active form, plasmin, in the presence of the exogenous urokinase activator (uPA). The other components of both cascade and extracellular matrix were not cleaved by Pic. We believe that the E. coli bacterium producing serinoprotease Pic binds to the extracellular matrix through several components, thus facilitating the infectious process in the host. Plasmin generated in the presence of Pic should also contribute to a synergistic effect on the degradation of complement system molecules, as well as to deregulated and increased activation of the blood coagulation cascade.